A biodesign based study on chronic tinnitus and evaluation of adaptive noise cancellation technology in its management - Sridhar, Shreya; Madhuri K R; Shah, Shreyas; Chaturvedi, Jagdish; Vijayarajan, A; Appaji, Abhishek M (2016 8th International Conference on Communication Systems and Networks (COMSNETS), 2016)
Advancements in technology have aided doctors and patients alike. However, there are always unmet needs and gaps in the market to be filled. In the audiology space, despite many technologies that address tinnitus, successfully implementing a solution for tinnitus is one such challenge. Tinnitus is the perception of sound in the absence of an acoustic stimulus and is heard only by the patient. It has an estimated prevalence of 50 – 70 million people in India, and about 17% of the world population develops this condition sometime in their life. There is a need for a solution that is affordable, and accessible to the majority population. In this study, a structured unmet needs analysis process that is based along the lines of the Biodesign approach has been employed to study and assess this unmet need. An understanding of the current treatment gaps and stakeholder analysis was done, which led to the formulation of a detailed need specification. The proposed concept involves determination of the subject's tinnitus frequency and pitch followed by the application of adaptive noise cancellation techniques to eliminate the noise heard by patient in real time. The implementation of the Biodesign methodology, scientific research on Tinnitus, a technical feasibility study was performed and results of the initial concept study is presented in this paper.